Twin Pregnancy discordordant for Downs syndrome: Case Report - Dinu-Florin Albu; Cristina-Crenguta Albu; Stefan-Dimitrie Albu (International Journal of Medical Research and Review, 2015)
The work presented is a clinical and genetical trial of a couple with a reproductive failure and a family history of chro-mosomal abnormalities. The most reliable and accurate methods used for antenatal diagnosis of Down syndrome fetuses are highlighted.